DEVELOPMENT STRATEGY OF JOGGING TRACK AS TOURIST ATTRACTION IN ANGGABAYA VILLAGE, PENATIH DENPASAR - Wirawan, Putu Eka; Sudiarta, I Nyoman (Institut Pariwisata dan Bisnis Internasional, 2018)
Development of tourism destination should be supported by the potential of tourism activities; one of them is sports tourism. Sports tourism is a tourism activity by doing sports activities as a fundamental and significant part of a vacation. Sanur Tourism Destination, known by many tourists as a place where they can perform sports activities as a mode of movement, has tourism potential that supports the development of sports tourism. That potential is also supported by the planning and activities of stakeholders in order to develop this tourism for society and tourists in realizing sustainable tourism (green tourism). The purposes of this research were: 1) to discover the potential that makes Sanur Tourism Destination has the opportunity to develop cycling tourism. 2) to find out the benefits of cycling tourism towards Sanur Tourism Destination. The research methodology used was descriptive research methodology. It aimed to obtain a complete profile or description of relevant aspects of an interesting phenomenon, which occurs in an individual, organization, industry, or other things. Techniques for collecting the data were direct observation, in-depth interview and documentation/literature studies.The results showed that: 1) the potential that makes Sanur Tourism Destination has the opportunity to develop cycling tourism. 2) the benefits of cycling tourism towards Sanur Tourism Destination. The recommendation of this research is expected to provide input to Stakeholder and Government in analyzing the potential of Sanur Tourism Destination in developing sports tourism as a friendly destination both in its activities and way of traveling, therefore, it is useful for the welfare of society. The results of this research could also help local people and government in reviewing the strategy of sports tourism planning in Sanur Tourism Destination in realizing sustainable tourism planning.